2022
DOI: 10.47992/ijcsbe.2581.6942.0175
|View full text |Cite
|
Sign up to set email alerts
|

Customer Perception towards Online Food Delivery Services- Development of Conceptual Model

Abstract: Purpose: The central idea of the paper is to study the influencing factors that shape the customer perception of online food delivery services and develop a conceptual model based on established customer theories and systematic literature review. Design: Secondary data is collected from books and journal papers using search engines such as Google Scholar, Research gate, SSRN, Base, Semantics and Inflibnet. Postulates and affecting factors to customer perception are proposed using the focus group interaction me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 204 publications
0
19
0
Order By: Relevance
“…When choosing food items from the FDAs, the customer's budget is a crucial consideration. A study found that consumers check prices when browsing various websites and choose goods with lesser pricing to be satisfied with their purchase (Frederick & Bhat, 2021). One of the key factors to keep clients, besides pricing, is delivery time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When choosing food items from the FDAs, the customer's budget is a crucial consideration. A study found that consumers check prices when browsing various websites and choose goods with lesser pricing to be satisfied with their purchase (Frederick & Bhat, 2021). One of the key factors to keep clients, besides pricing, is delivery time.…”
Section: Discussionmentioning
confidence: 99%
“…Customers are influenced to choose FDA services by the order's speed, simplicity, and accuracy (Ling et al, 2021). Any delivery delay longer than expected will lower customer satisfaction, regardless of the road or the weather (Frederick & Bhat, 2021). Additionally, it was found in a study that knowing the routes is crucial for prompt delivery, which results in customer satisfaction when using FDAs (Jaroenwanit et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations